Age‐dependent expression of Nav1.9 channels in medial prefrontal cortex pyramidal neurons in rats. Issue 12 (22nd September 2017) - Gawlak, Maciej; Szulczyk, Bartłomiej; Berłowski, Adam; Grzelka, Katarzyna; Stachurska, Anna; Pełka, Justyna; Czarzasta, Katarzyna; Małecki, Maciej; Kurowski, Przemysław; Nurowska, Ewa; Szulczyk, Paweł
ABSTRACT: Developmental changes that occur in the prefrontal cortex during adolescence alter behavior. These behavioral alterations likely stem from changes in prefrontal cortex neuronal activity, which may depend on the properties and expression of ion channels. Nav1.9 sodium channels conduct a Na + current that is TTX resistant with a low threshold and noninactivating over time. The purpose of this study was to assess the presence of Nav1.9 channels in medial prefrontal cortex (mPFC) layer II and V pyramidal neurons in young (20‐day old), late adolescent (60‐day old), and adult (6‐ to 7‐month old) rats. First, we demonstrated that layer II and V mPFC pyramidal neurons in slices obtained from young rats exhibited a TTX‐resistant, low‐threshold, noninactivating, and voltage‐dependent Na + current. The mRNA expression of the SCN11a gene (which encodes the Nav1.9 channel) in mPFC tissue was significantly higher in young rats than in late adolescent and adult rats. Nav1.9 protein was immunofluorescently labeled in mPFC cells in slices and analyzed via confocal microscopy. Nav1.9 immunolabeling was present in layer II and V mPFC pyramidal neurons and was more prominent in the neurons of young rats than in the neurons of late adolescent and adult rats. We conclude that Nav1.9 channels are expressed in layer II and V mPFC pyramidal neurons and that Nav1.9 protein expression in the mPFC pyramidal neurons of late adolescent and adult rats is lower than that in the neurons of young rats. © 2017 Wiley Periodicals, Inc. Develop Neurobiol 77: 1371–1384, 2017